2020
DOI: 10.1093/cercor/bhaa371
|View full text |Cite
|
Sign up to set email alerts
|

Transdiagnostic, Connectome-Based Prediction of Memory Constructs Across Psychiatric Disorders

Abstract: Memory deficits are observed in a range of psychiatric disorders, but it is unclear whether memory deficits arise from a shared brain correlate across disorders or from various dysfunctions unique to each disorder. Connectome-based predictive modeling is a computational method that captures individual differences in functional connectomes associated with behavioral phenotypes such as memory. We used publicly available task-based functional MRI data from patients with schizophrenia (n = 33), bipolar disorder (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 45 publications
(40 reference statements)
3
31
0
Order By: Relevance
“…Consistent with our findings, previous transdiagnostic studies have reported common disrupted patterns of functional connectivity across mental disorders (Baker et al, 2019; Barron et al, 2020; Ma et al, 2020; Qi et al, 2020; Xia et al, 2018). Moreover, recent studies have demonstrated that the overall psychopathology factor is associated with abnormalities of both within- and between-network functional connectivity (Elliott et al, 2018; Karcher et al, 2020; Kebets et al, 2019).…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with our findings, previous transdiagnostic studies have reported common disrupted patterns of functional connectivity across mental disorders (Baker et al, 2019; Barron et al, 2020; Ma et al, 2020; Qi et al, 2020; Xia et al, 2018). Moreover, recent studies have demonstrated that the overall psychopathology factor is associated with abnormalities of both within- and between-network functional connectivity (Elliott et al, 2018; Karcher et al, 2020; Kebets et al, 2019).…”
Section: Discussionsupporting
confidence: 93%
“…To further improve the interpretability of our findings, we examined network anatomy in a similar manner to previous studies (Barron et al., 2020 ; Lake et al., 2019 ). Briefly, we computed the probability that iFCs are shared between the networks identified by our prediction model and within or between nine canonical RSNs.…”
Section: Methodsmentioning
confidence: 99%
“…For predictive modeling, a multidimensional approach was employed, which combines multiple connectomes and behavioral measures into a single predictive modeling framework. 25 Given that a single behavioral measurement represents a noisy approximation of any behavioral construct, and there were six craving ratings (i.e., before and after each imagery script), a principal components analysis (PCA) was used to summarize craving in a data-driven manner for predictive modeling with CPM. To maintain separate train and test groups, for each iteration, each PCA was limited to the training datasets and the PCA coefficients applied to the test dataset.…”
Section: Predictive Modeling Frameworkmentioning
confidence: 99%
“…19,20 CPM is also data-driven, and is therefore used to identify neural 'signatures' in functional-connectivity data related to a specific phenotype. 18,21 CPM has been used to predict cognitive and clinical phenotypes, [22][23][24][25] and, more recently, has been used to predict treatment outcomes in SUDs. 26,27 This study aimed to identify a transdiagnostic 'craving network' by applying CPM to functional connectivity data in individuals with and without substance-use-related conditions, to predict a continuous measure of self-reported craving.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation